Gambaran Stigma HIV pada Perempuan PKK Desa Banaran, Kecamatan Grogol, Kabupaten Sukoharjo - Rosa Marita Krisnawati; Titik Haryanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Stigma against HIV/AIDS patients (ODHIV) remains a significant issue in society, particularly among PKK (Family Welfare Movement) women. The purpose of this study is to describe the stigma that arises among PKK women toward (PLWHA) in Banaran Village, Grogol Sub-district, Sukoharjo Regency. Qualitative research using a phenomenological approach is the methodology employed. Information was gathered by conducting in-depth conversations with two PKK members and one HIV program officer from Grogol Health Center. The results indicate that the knowledge of PKK women about HIV/AIDS is still limited and tends to be general, although they do understand some basic aspects of HIV transmission. Stigma manifests in the form of negative prejudice, social exclusion, and excessive, unfounded fear of HIV transmission through physical contact. This lack of understanding is exacerbated by misinformation from social media and societal norms that reinforce moral stigma. The main cause of this kind of stigma is a lack of education. Therefore, educational efforts and the empowerment of PKK women as agents of change are essential to disseminate accurate information about HIV/AIDS. Empathetic, community-based education is a crucial step in reducing stigma and increasing social acceptance of people living with HIV.